2021
DOI: 10.2106/jbjs.21.00179
|View full text |Cite
|
Sign up to set email alerts
|

A Matched Comparison of the Long-Term Outcomes of Cemented and Cementless Total Knee Replacements

Abstract: Background: Total knee replacement (TKR) can be implanted with or without the use of cement. It is currently unknown how cemented and cementless TKRs compare overall and in different age groups of the population in the long term. Methods:The National Joint Registry collects information on knee replacements inserted in England, Wales, Northern Ireland and Isle of Man and was linked for multiple confounders to the National Health Service Hospital Episode Statistics database. Using propensity matched scoring tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Similarly, a multicenter study of 605 cementless and 605 cemented Stryker TKAs by Yazdi et al [20] showed no difference in reoperation rates and higher rates of aseptic revision rates in the cementless (1.2%) versus the cemented (0.8%) cohort ( P = .294). However, several registry studies have reported a 1% to 2% higher rate of early failure of cementless TKAs compared with cemented TKAs due to fracture or failure of bony ingrowth, similar to our findings [12,15,18]. In the cementless cohort, 2 patients (1.2%) underwent early revision for aseptic loosening compared with none in the cemented cohort.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, a multicenter study of 605 cementless and 605 cemented Stryker TKAs by Yazdi et al [20] showed no difference in reoperation rates and higher rates of aseptic revision rates in the cementless (1.2%) versus the cemented (0.8%) cohort ( P = .294). However, several registry studies have reported a 1% to 2% higher rate of early failure of cementless TKAs compared with cemented TKAs due to fracture or failure of bony ingrowth, similar to our findings [12,15,18]. In the cementless cohort, 2 patients (1.2%) underwent early revision for aseptic loosening compared with none in the cemented cohort.…”
Section: Discussionsupporting
confidence: 88%
“…However, the advent of porous metal ingrowth surfaces that use 3-dimensional printing and manufacturing holds the promise of improved biologic fixation and has renewed interest in cementless implants [2,3,17,19]. Registry data from the United Kingdom suggested improved 10-year survivorship with cementless TKA, albeit with slightly higher revision rates compared with cemented TKA [12].…”
Section: Introductionmentioning
confidence: 99%
“…Factors used for matching included BMI, age, sex, Charlson comorbidity index, American Society of Anesthesiologists (ASA) grade, year of surgery, bone graft usage, surgical indication, venous thromboembolism (VTE) prophylaxis, ethnicity, rural/urban location, admission type, deprivation indices, and UKR surgeon caseload. Surgeon caseload was defined as the mean number of UKRs performed per year as described previously 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there are continued interests in cementless TKA for biological ixation. Recent systematic reviews and meta-analyses show that cementless TKA had implant survivorship comparable to cemented TKA [7,10,20,21,33]. Concerning radiographical results of cementless TKAs, Hasan et al and Sporer et al noted that tibial migrations were largest within the irst six weeks and three months postoperatively, respectively, and further migrations had not appeared at 2 years postoperatively [13,30].…”
Section: Discussionmentioning
confidence: 99%